Remote activation and detection of up-converted luminescence via surface plasmon polaritons propagating in a silver nanowire. Issue 26 (27th June 2018) - Prymaczek, A.; Cwierzona, M.; Grzelak, J.; Kowalska, D.; Nyk, M.; Mackowski, S.; Piatkowski, D.
Abstract : In this paper we demonstrate remote activation and detection of the 2-photon up-conversion luminescence via surface plasmon polaritons propagating in a long silver nanowire. Abstract : In this paper, we demonstrate remote activation and detection of the 2-photon up-conversion luminescence via surface plasmon polaritons propagating in a long silver nanowire. The hybrid nanostructure was assembled by locally depositing a submicron droplet of nanocrystal-containing colloidal solution on one of the ends of the metallic nanowire. When – using a classic confocal microscope – the second end of the nanowire, without the nanocrystals, is illuminated with infrared laser light, we observe strong emission from the same end. Therefore, it indicates that surface plasmon polaritons activated with infrared light at the second end of the nanowire propagate along it and can excite nanocrystals in the droplet at the opposite end. Subsequently, the excited nanocrystals up-convert the energy and by launching surface plasmon polaritons can guide the up-converted luminescence back to the starting point. The emergence of this effect is much more pronounced for a laser polarized along the nanowire. The spectral and temporal character of this emission reveals strong interactions between surface plasmon polaritons and electronic states of the nanocrystals. The details of local and non-local aspects of the effects of remote excitation and guiding of energy in a silver nanowire are elucidated using a unique experimental setup, based on two microscope objectives for spatial separation and control of both excitation and emission beams.